The Myelin Water Fraction Serves as a Marker for Age-Related Myelin Alterations in the Cerebral White Matter – A Multiparametric MRI Aging Study - Faizy, Tobias D.; Thaler, Christian; Broocks, Gabriel; Flottmann, Fabian; Leischner, Hannes; Kniep, Helge; Nawabi, Jawed; Schön, Gerhard; Stellmann, Jan-Patrick; Kemmling, André; Reddy, Ravinder; Heit, Jeremy J.; et al. (Frontiers in Neuroscience, 2020)
Quantitative MRI modalities, such as diffusion tensor imaging (DTI) or magnetization transfer imaging (MTI) are sensitive to the neuronal effects of aging of the cerebral white matter (WM), but lack the specificity for myelin content. Myelin Water Imaging (MWI) is highly specific for myelin and may be more sensitive for the detection of changes in myelin content inside the cerebral WM microstructure. In this multiparametric imaging study, we evaluated the performance of Myelin Water Fraction (MWF) estimates as a marker for myelin alterations during normal-aging. Multiparametric MRI data derived from DTI, MTI and a novel, recently-proposed MWF-map processing and reconstruction algorithm were acquired from 54 healthy subjects (aged 18-79 years) and region-based multivariate regression analysis was performed. MWFs significantly decreased with age in most WM regions (except corticospinal tract) and changes of MWFs were associated with changes of Radial Diffusivity (RD), indicating either substantial alterations or preservation of myelin content in these regions. Decreases of Fractional Anisotropy (FA) and Magnetization Transfer Ratio (MTR) were associated with lower MWFs in commissural fibre tracts only. Mean diffusivity (MD) had no regional effects on MWF. We conclude that MWF estimates are sensitive for the assessment of age-related myelin alterations in the cerebral WM of normal-aging brains.